Tradisi Larangan Menikah dengan Orang Sekaum dengan Mantan Pasangan di Nagari Padang Laweh Perspektif ‘Urf - Lestari; Shafra (Lembaga Yasin AlSys, 2026)
Although customary marriage traditions have been widely studied, research on the prohibition against marrying a member of a former spouse’s clan, whether following divorce or the spouse’s death, and its status from the perspective of ‘urf remains limited. This study aimed to analyze the implementation of the tradition prohibiting marriage to a member of a former spouse’s clan in Nagari Padang Laweh, Koto VII Subdistrict, Sijunjung Regency, and to determine its status from the perspective of ‘urf. This study employed a qualitative approach using field research. Informants were selected purposively, while data were collected through interviews and observation. The data were analyzed descriptively and inductively through the stages of transcription, data categorization, description of the findings, and conclusion drawing. The findings showed that the prohibition applied to men and women whose marriages had ended through either divorce or the death of their spouse, preventing them from marrying a member of their former spouse’s clan. This tradition aims to preserve raso, family harmony, clan honor, and interclan relations and is accompanied by the imposition of customary sanctions on violators. From the perspective of ‘urf, the tradition is categorized as ‘urf ‘amali based on its form and ‘urf khāṣṣ based on its scope and may be regarded as ‘urf ṣaḥīḥ provided that its implementation does not conflict with Islamic law. These findings clarify the status of this tradition while broadening the understanding of the relationship between customary norms and Islamic law in the marital practices of the Minangkabau community.